And yet... Unstable circumference of the critical function - Croce, Marcela (2024)
The literary criticism admits multiple discursive supports. Although it is usual to associate the term ‘criticism’ with the argumentative academic article, its exercise extends to other genres, whose relative lack of definition or ‘minor’ character allows them to advance in domains of uncertain limits. Instead of equating criticism exclusively with the form in which its professional practice is manifested, here we propose to establish the critical function as a common denominator of texts that are inscribed in genres such as the essay, the prologue, the chronicle, and the epistolary (when these are produced between intellectuals who postulate evaluative judgements or cultural and editorial projects). In addition to a brief phenomenology of each form, this paper evaluates specific examples in which the critical function is verified in the Latin American context. To this end, it analyses an essay by Eduardo Grüner, the most quoted prologue to the work of Frantz Fanon, Ángel Rama’s correspondence with multiple correspondents on the continent, and the chronicles of Sergio Pitol, Carlos Monsiváis and María Moreno.